Effect of AB Mix Concentration on Height and Leaf Number of Hydroponic Ipomea reptans - Tyas Indriasari; Hemalia Susanti; Melinda Agustina; Mutia Zakiyyatus Sabrina; Suwarto Suwarto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Ipomoea reptans is a widely consumed leafy vegetable with high potential for hydroponic cultivation, which is greatly influenced by nutrient management. This study aims to determine the effect of various AB Mix solutions with different concentrations on plant growth and to identify the optimal concentration for plant development. The experiment was conducted in a greenhouse at Universitas Veteran Bangun Nusantara Sukoharjo using a completely randomized design (CRD) with three concentrations of AB Mix solution: high (5 ml/l), medium (3 ml/l), and low (1.5 ml/l), with five replicates for each treatment. Plant height and number of leaves were observed as growth parameters. Data were analyzed using one-way ANOVA at a 5% significance level, followed by Tukey's post hoc test. The results showed that various concentrations of AB Mix significantly affected plant height and number of leaves (P<0.05). The medium concentration (3 ml/l) showed the highest plant height and number of leaves compared to the other treatments. It can be concluded that a 3 ml/l AB Mix nutrient concentration is the most optimal for promoting the vegetative growth of Ipomoea reptans in hydroponic conditions and can be recommended as a practical guide for hydroponic cultivation to enhance plant vegetative growth.